2014
DOI: 10.1371/journal.pone.0086777
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XVI Induces Expression of MMP9 via Modulation of AP-1 Transcription Factors and Facilitates Invasion of Oral Squamous Cell Carcinoma

Abstract: Collagen XVI belongs to the family of fibril-associated collagens with interrupted triple helices (FACIT). It is overexpressed during the progression of oral squamous cell carcinoma (OSCC). The present data show a strong collagen XVI-dependent induction of MMP9 and an increase in OSCC cell invasion. We found activated integrin-linked kinase (ILK) in a complex with kindlin-1 and activation of protein kinase B (PKB/Akt) to be responsible for MMP9 induction. Inhibition of the formation of focal adhesions reduced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Prior to transduction, the hTIM-4-expresssing HEK 293 stable cell line was incubated at 37°C for 30 min with increasing concentrations of arginyl-glycylaspartic acid (RGD) peptide (Abbiotec) or 3.47 inhibitor (a kind gift from Kartik Chandran, Albert Einstein College of Medicine). Concentrations were based on amounts that have been previously demonstrated to inhibit integrin binding (RGD peptide) or EBOV entry (3.47) (38)(39)(40). Cells in the presence of the inhibitor were transduced with FL EBOV VSV-GFP pseudovirions (MOI of 0.7 [titer determined on Vero cells]).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to transduction, the hTIM-4-expresssing HEK 293 stable cell line was incubated at 37°C for 30 min with increasing concentrations of arginyl-glycylaspartic acid (RGD) peptide (Abbiotec) or 3.47 inhibitor (a kind gift from Kartik Chandran, Albert Einstein College of Medicine). Concentrations were based on amounts that have been previously demonstrated to inhibit integrin binding (RGD peptide) or EBOV entry (3.47) (38)(39)(40). Cells in the presence of the inhibitor were transduced with FL EBOV VSV-GFP pseudovirions (MOI of 0.7 [titer determined on Vero cells]).…”
Section: Methodsmentioning
confidence: 99%
“…50 AP1 has been reported to increase the transcription of MMP9, 69,70 while EGFR and integrins enhance MMP9 activity. [71][72][73][74][75] Furthermore, MMP9 degrades type IV collagen and promotes HNSCC invasion.…”
Section: Mmps In Hnscc Invasionmentioning
confidence: 98%
“…3B). It has been reported that MMP9 is associated with cell proliferation and invasion in cancers [35][36][37]. To explore whether MMP9 is associated with CCL5/CCR5-Akt pathway, the expression of MMP9 was also assessed by western blot analysis.…”
Section: Involvement Of P-akt In Ccr5-mediated Proliferation and Invamentioning
confidence: 99%